Variation in adult and pup wolf diets at natal den sites is influenced by forest composition and configuration. Issue 1 (11th January 2023) - Roffler, Gretchen H.; Pilgrim, Kristine L.; Zarn, Katherine E.; Schwartz, Michael K.; Levi, Taal
Abstract: Although wolves are wide‐ranging generalist carnivores throughout their life cycle, during the pup‐rearing season wolf activity is focused on natal den sites where pup survival depends upon pack members provisioning food. Because prey availability is influenced by habitat quality within the home range, we investigated the relative importance of prey species for adults and pups and further examined the relationship between habitat characteristics, wolf diet, and litter size on Prince of Wales Island (POW) in Southeast Alaska. During 2012–2020, we detected 13 active den sites within the home ranges of nine wolf packs. We estimated minimum pup counts using motion‐detecting cameras and individual genotypes from noninvasive samples (hair: n  = 322; scat: n  = 227) and quantified wolf diet composition using fecal DNA metabarcoding ( n  = 538). We assessed habitat composition, configuration, and connectivity within denning and annual home ranges estimated using wolf GPS‐collar data. Contrary to expectations, wolves had a more constricted diet during denning season (April 15–July 31), and within this season pups had a narrower dietary niche (species richness [ S ] = 4) focused more on deer (relative frequency of occurrence [O/I] = 0.924) than adults ( S  = 15; deer O/I = 0.591). Litter size had a positive relationship with the relative frequency of deer in a wolf pack's diet. Wolf consumption of deer was positively associated with the proportion of young‐growth forest (≤25 years old) within denning and annual home ranges. High levels of vegetation patch interspersion, and the density of closed logging roads were also important predictors, suggesting these habitat qualities were influential for increasing the availability of deer to wolves. Our results contrast with previous research indicating wolf pup diets included more alternate prey (i.e., beaver) than adults and emphasize the importance of deer to wolf viability on POW, especially during denning season. Abstract : Despite demonstrated dietary plasticity throughout their life cycle, wolves had a narrow dietary niche during the denning season focused on Sitka black‐tailed deer ( Odocoileus hemionus sitkensis ), and pups nearly exclusively consumed deer during their first 2 months of life. Wolf consumption of deer was influenced by the availability of early successional forest, closed logging road density, and forest patchiness, suggesting these habitat qualities were influential for increasing the availability of deer to wolves. The contribution of deer in wolf diets had a positive effect on litter size providing a link to wolf fitness.